Identification of Capsular Types in Carbapenem-Resistant Klebsiella pneumoniae Strains by wzc Sequencing and Implications for Capsule Depolymerase Treatment - Pan, Yi-Jiun (Antimicrob Agents Chemother, 2015)
Klebsiella pneumoniae is an important human pathogen associated with a variety of diseases, and the prevalence of multidrug-resistant K. pneumoniae (MDRKP) is rapidly increasing. Here we determined the capsular types of 85 carbapenem-resistant K. pneumoniae (CRKP) strains by wzc sequencing and investigated the presence of carbapenemases and integrons among CRKP strains. Ten CRKP strains (12%) were positive for carbapenemase (imipenemase, 6/85 strains; K. pneumoniae carbapenemase, 3/85 strains; Verona integron-encoded metallo-β-lactamase, 1/85 strains). Capsular type K64 accounted for 32 CRKP strains (38%), followed by K62 (13%), K24 (8%), KN2 (7%), and K28 (6%). Sequence types (STs) were determined by multilocus sequence typing (MLST), and the results indicated that ST11, which accounted for 47% of these CRKP strains (40/85 strains), was the major ST. We further isolated a K64-specific capsule depolymerase (K64dep), which could enhance serum and neutrophil killing in vitro and increase survival rates for K64 K. pneumoniae-inoculated mice. The toxicity study demonstrated that mice treated with K64dep showed normal biochemical parameters and no significant histopathological changes of liver, kidney, and spleen, indicating that enzyme treatment did not cause toxicity in mice. Therefore, the findings of capsular type clustering among CRKP strains and effective treatment with capsule depolymerase for MDRKP infections are important for capsule-based vaccine development and therapy.